2004
DOI: 10.1093/nar/gkh989
|View full text |Cite
|
Sign up to set email alerts
|

Formation of 8-oxo-7,8-dihydroguanine-radicals in  -irradiated DNA by multiple one-electron oxidations

Abstract: Electron spin resonance (ESR) studies of radicals formed by radiation-induced multiple one-electron oxidations of guanine moieties in DNA are reported in this work. Annealing of gamma-irradiated DNA from 77 to 235 K results in the hydration of one electron oxidized guanine (G*+) to form the 8-hydroxy-7,8-dihydroguanin-7-yl-radical (*GOH) having one beta-proton coupling of 17-28 G and an anisotropic nitrogen coupling, A(parallel), of approximately 20 G, A(perpendicular) = 0 with g(parallel) = 2.0026 and g(perpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
93
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 53 publications
9
93
0
1
Order By: Relevance
“…(Unfortunately, the presence of overlapping spectra in the Hx system prevented direct observation of the transformation during the controlled warming experiments.) This is like the behavior described by Shukla et al in solid DNA (15) and the behavior proposed by Reynisson and Steenken in a density functional theory-based computational examination of probable reactions between water and oxidized guanine or adenine (21). The latter group also found that calculations on a structure with H 2 O added to the C8 position of • Gua ϩ simply led to separation of the water from the • Gua ϩ .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…(Unfortunately, the presence of overlapping spectra in the Hx system prevented direct observation of the transformation during the controlled warming experiments.) This is like the behavior described by Shukla et al in solid DNA (15) and the behavior proposed by Reynisson and Steenken in a density functional theory-based computational examination of probable reactions between water and oxidized guanine or adenine (21). The latter group also found that calculations on a structure with H 2 O added to the C8 position of • Gua ϩ simply led to separation of the water from the • Gua ϩ .…”
Section: Discussionsupporting
confidence: 83%
“…In addition to reproducing the coupling values well for RIII, the computations based on the geometry-optimized Structure IV also predicted the dipolar vector for ␤-coupling RIII 2 paralleling that of the experimental result (in Table 3) within 3Њ. As well, a recent report on the • GOH species (with no evidence for protonation at N7) in DNA found the ␤-HC8 coupling to cover the range 17-28 G (ϳ48-78 MHz) (15), which includes the value reported here for Hx and previously for Gd. In summary, therefore, the body of evidence clearly indicates that RIII has the chemical form shown as Structure IV.…”
Section: Radical Riii: the C8 Oh-addition Radicalsupporting
confidence: 71%
“…Among DNA bases, guanine has the lowest redox potential, and so it is easily oxidized to 8-oxo-7,8-dihydroguanine (8-oxoG) via two-electron oxidation (Shukla et al, 2004). The key repair enzyme that excises 8-oxoG from cellular DNA (8-oxoG: C base pairs) is the 8-oxoguanine DNA glycosylase (OGG1) (Hazra et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] The proposed mechanism consists of attack of H 2 O at the C8 position of GC + (followed by deprotonation of the adduct). This leads to a neutral radical (GOH)C as an intermediate product [27] that is prone to further oxidation. A one-electron abstraction from (GOH)C leads to a nonradical cationic intermediate, (GOH) + , which transforms into an 8-oxoG residue after the loss of a second proton.…”
Section: Introductionmentioning
confidence: 99%